Profile of Students’ Cognitive Ability in Chemistry Learning using Chemistry Systemic Multiple Choice Questions (CSMCQs) - Primastuti, Metridewi; Priyambodo, Erfan (EDUCATUM Journal of Science, Mathematics and Technology, 2018)
The systemic approaches connect a set of interacting, functioning, and interdependent or elements with mutual relationships. The objective of this study is to analyze how students' cognitive ability profiles if measured using Chemistry Systemic Multiple Choices Questions (CSMCQs). This study was conducted by testing CSMCQs to the 157 students who studied with the usual learning approaches by teachers. Data collection technique were conducted using the objective test instruments consist of C1 to C6 cognitive abilitiy domains. Data were analyzed using descriptive percentage analysis. The results showed that students' cognitive ability is in the highest category. Based on these result, Chemistry Systemic Multiple Choice Questions (CSMCQs) can be used as an alternative learning evaluation instrument to develop students’ cognitive abilities.